2023
DOI: 10.1021/acsami.3c02501
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoresponse of High Crystalline Bi2Se3 Thin-Films Using Patterned Substrates

Abstract: High-quality Bi2Se3 thin films with topological insulating properties at room temperature have recently attracted much attention as one of the promising materials for realizing innovative electronic and optoelectronic devices. Here, we report the high crystallinity growth of Bi2Se3 thin films on a patterned sapphire substrate (PSS) by using a vapor-phase transport deposition with minimizing thermal dissociation of Se atoms vaporized in Bi2Se3 powder. This PSS not only reduces the large dislocation of heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…[5][6][7][8][9][10][11] These studies have revealed unique photoresponse characteristics, including high photoresponsivity and ultrafast relaxation times, and it is also found that the occupied surface states often occur in the midgap of Bi 2 Se 3 , while unoccupied surface states emerge at higher energy levels, making Bi 2 Se 3 a promising candidate for optoelectronic applications. [12][13][14][15][16][17][18] Expanding on the potential of Bi 2 Se 3 and its surface states, the incorporation of a gold interlayer amidst topological layers may introduce an array of compelling functionalities. This interface not only influences and affects the surface charge density of the topological material but also modulates charge transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] These studies have revealed unique photoresponse characteristics, including high photoresponsivity and ultrafast relaxation times, and it is also found that the occupied surface states often occur in the midgap of Bi 2 Se 3 , while unoccupied surface states emerge at higher energy levels, making Bi 2 Se 3 a promising candidate for optoelectronic applications. [12][13][14][15][16][17][18] Expanding on the potential of Bi 2 Se 3 and its surface states, the incorporation of a gold interlayer amidst topological layers may introduce an array of compelling functionalities. This interface not only influences and affects the surface charge density of the topological material but also modulates charge transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Among these systems, Bi 2 Se 3 , a three-dimensional (3D) TI that possesses a large room-temperature energy gap of ∼0.3–0.35 eV in the bulk and high permittivity values, is an interesting TI material for photonic applications. ,, Previous theoretical and experimental investigations have indicated that Bi 2 Se 3 is a high refractive index (RI) material with the real part of the RI peaking around n ∼ 5.3–5.8 for the near-infrared (NIR) regime, depending on the number of layers, , while other studies have primarily focused on understanding the light–matter interaction in Bi 2 Se 3 within the NIR to mid-infrared (MIR) spectral ranges. However, experimentally measured fundamental properties such as permittivity, RI, and optical anisotropy in these TIs are still lacking in the infrared range as well as the photonic capabilities of both bulk and nanostructured Bi 2 Se 3 . Nanostructured systems and sub-wavelength resonators such as spheres, disks, and gratings provide an ideal platform for studying light–matter interactions with unprecedented control. Here, we study the MIR optical characteristics of TI Bi 2 Se 3 and utilize them to demonstrate high-index Mie-resonant nanostructures in chemical vapor deposition (CVD)-grown Bi 2 Se 3 nanobeams (NBs).…”
mentioning
confidence: 99%